1984
DOI: 10.1002/bbpc.19840880422
|View full text |Cite
|
Sign up to set email alerts
|

Nonequilibrium Phase Transitions with Hysteresis in Solid Catalysts. The System Copper‐Oxygen‐Propene

Abstract: Catalysis / Non-equilibrium Phenomena / Phase Transitions / SurfacesThe rates of formation of acrolein, CO, and CO from propene and oxygen on oxides of copper as catalysts have been investigated at P C ? H~ = 50 mbar, 4 mbar s po, 5 200 mbar in a differential reactor at 645 and 735 K. Oxygen contents of the catalysts have been determined in sltu by titration with H, at 713 K. Selectivity and rate of oxygen consumption at steady state of the catalyst are not single valued functions of gas phase composition. Mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
1
0

Year Published

1984
1984
1996
1996

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 15 publications
2
1
0
Order By: Relevance
“…During this study, a very particular phenomenon had been observed. Similar bistability and/or oscillatory phenomena have also been observed in other reaction systems using copper as catalyst (Greger et al, 1984;Amariglio et al, 1989). We had found that part of the activity was recovered when the oxygen pressure was lowered below a critical value ("lower critical oxygen pressure, p,"), indicating that the loss of activity was not irreversible as had been indicated by Thomas et al (1980).…”
supporting
confidence: 74%
See 2 more Smart Citations
“…During this study, a very particular phenomenon had been observed. Similar bistability and/or oscillatory phenomena have also been observed in other reaction systems using copper as catalyst (Greger et al, 1984;Amariglio et al, 1989). We had found that part of the activity was recovered when the oxygen pressure was lowered below a critical value ("lower critical oxygen pressure, p,"), indicating that the loss of activity was not irreversible as had been indicated by Thomas et al (1980).…”
supporting
confidence: 74%
“…There was thus a bistability in the regions between the higher and lower critical pressures, p h and p,. Similar bistability and/or oscillatory phenomena have also been observed in other reaction systems using copper as catalyst (Greger et al, 1984;Amariglio et al, 1989). In these studies, the interpretations were based on an assumption of a change of composition or structure of the catalyst surface.…”
supporting
confidence: 74%
See 1 more Smart Citation